CASE REPORTSSweet’s syndrome in Kostmann disease – association with pegfilgrastim - Lis-Święty, Anna; Brzeźińska-Wcisło, Ligia; Kyrcz-Krzemień, Sławomira; Rogala-Poborska, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Sweet’s syndrome is characterized by erythematous-oedematous lesions with neutrophilic infiltrate in the upper part of the dermis, often accompanied by fever and increased count of neutrophils in the peripheral blood. The forms induced by various medications: all-trans retinoic acid, carbamazepine, hydralazine, levonorgestrel/ethinyl estradiol, minocycline, trimethoprim/sulfamethoxazole and granulocyte colony-stimulating factor (G-CSF). A case of pegfilgrastim-induced (recombinant human G-CSF) Sweet’s syndrome in a 23-year-old woman with severe congenital neutropenia (SCN) (Kostmann disease) is presented. Thus far reports of G-CSF-induced Sweet’s syndrome have been related to patients treated because of complications in the course of haematological malignancies.